4-[2-(4-Chlorophenyl)hydrazinylidene]-3-methyl-5-oxo-4,5-dihydro-1H-pyrazole-1-carbothioamide - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title molecule, C(11)H(10)ClN(5)OS, an intramolecular N—H⋯O hydrogen forms an S(6) ring motif. The dihedral angle between the pyrazole ring and the benzene ring is 3.77 (8)°. In the crystal, molecules are linked by N—H⋯S and N—H⋯O hydrogen bonds into layers parallel to the bc plane.